FACULTY OF FOREIGN PHILOLOGY AT H.S. SKOVORODA KHNPU: НISTORY AND PRESENT - Борисов, В.; Князь, Г. (New Collegium, 2020)
The article deals with the history of the Faculty of Foreign Philology at H.S. Skovoroda Kharkiv National Pedagogical University from origins to the present. The main directions of the faculty are figured out: academic, scientific, methodological, educational work; engagement in international exchange projects and programs; development and compilation of manuals and textbooks. At the faculty, it is traditional to hold scientific and practical conferences and discussion clubs among students who study foreign languages. An important aspect in the work of the faculty is cooperation with schools (participation in Olympiads, preparation of the Junior Academy of Sciences research papers, holding methodological seminars). Educational work being an integral part of the educational process enables qualitative training of a future foreign language teacher in the context of New Ukrainian School.